Trichodinids (Ciliophora) of Corydoras paleatus (Siluriformes) and Jenynsia multidentata (Cyprinodontiformes) from Argentina, with description of Trichodina corydori n. sp. and Trichodina jenynsii n. sp - Marcotegui, Paula Soledad (2016)
During surveys of parasites of the pepper cory Corydoras paleatus Jenyns, 1842 and sided-livebearer Jenynsia multidentata Jenyns, 1842 from Samborombón River, Argentina, Trichodina corydori n. sp., Trichodina cribbi Dove and O’Donoghue, 2005 and T. jenynsii n. sp. were morphologically studied. Taxonomic and morphometric data for these trichodinids based on dry silver nitrate-impregnated specimens are presented. Trichodina corydori is characterized by a prominent blade apophysis, the section connecting the blade and central part is short, and the adoral ciliary spiral makes a turn of 370-380°. Trichodina jenynsii is characterized by curved blades and prominentlyshaped denticle rays that are characteristically extremely long, tapering to thin sharp points in adult specimens. This study is the first formal report of these trichodinids from South America, and the description of two new species.